Clinical update on cutaneous and subcutaneous sarcomas. (26th September 2022) - Kumari, Jyoti; Das, Kinnor; Patil, Anant; Babaei, Mahsa; Cockerell, Clay J.; Goldust, Mohamad
Abstract: Background: Cutaneous sarcomas are uncommon cancers that can have a wide range of clinical symptoms and lead to considerable cutaneous as well as systemic morbidity. Aim: The objective of this review article is to discuss epidemiology, clinical features, diagnosis, and therapy of different types of cutaneous sarcomas. Material and methods: Literature was screened to retrieve articles from PubMed/Medline and Google Scholar and related websites. Cross‐references from the relevant articles were also considered for review. Review articles, clinical studies, systematic reviews, meta‐analyses, and relevant information from selected websites were included. Results and discussion: Cutaneous sarcomas have a negative effect on the quality of life. In their diagnosis, clinical presentation and histological evaluation are crucial. Complete surgical removal is the solution for more or less all cutaneous and subcutaneous sarcomas. The prognosis for cutaneous sarcomas is generally favorable since they tend to recur locally with distant metastases only on rare occasions. Patients having advanced disease should be treated in the setting of clinical trials if possible; choices include radiation therapy and systemic medicines. The value of innovative immunotherapy cannot be determined decisively at this time due to a paucity of relevant trials. Conclusion: As cutaneous sarcomas are rarely diagnosed based on clinical findings, histology plays an important role in the diagnosis. They have a relatively favorable prognosis if treated properly. Patients should be treated at specialized centres.